2021
DOI: 10.1021/acsami.1c13096
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Alternating Photoluminescence Segmentation in Hexagonal Monolayer Tungsten Disulfide Grown by Physical Vapor Deposition

Abstract: Two-dimensional semiconductors exhibit strong light emission under optical or electrical pumping due to quantum confinement and large exciton binding energies. The regulation of the light emission shows great application potential in nextgeneration optoelectronic devices. Herein, by the physical vapor deposition strategy, we synthesize monolayer hexagonal-shaped WS 2 , and its photoluminescence intensity mapping show three-fold symmetric patterns with alternating bright and dark regions. Regardless of the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…Molybdenum disulfide (MoS 2 ) as the typical member of two-dimensional (2D) transition metal dichalcogenides (TMDCs) has attracted tremendous attention due to its rich physical/chemical properties, such as layer-dependent electronic structure, layer-dependent photoexcitation, high mobility, and reasonable band gap. Different than other 2D TMDCs, MoS 2 is earth-abundant and environmentally stable. Thus, it has been considered as a promising candidate for post-Moore’s law era. The recent development, such as construct MoS 2 transistors with 1 nm channel, MoS 2 circuits, and MoS 2 room photodetectors with detection range from visible to near-infrared, exhibits its potentials in novel applications like electronic and optoelectronic devices. , Although the monolayer MoS 2 has gained more investigation, more and more research demonstrated that the device based on few-layer MoS 2 has a higher device carrier mobility caused by the lower contact resistance, which is one of the most important factors when evaluating the semiconductor devices. Besides the thickness factor, the electrical property of few-layer MoS 2 is also related to its stacking orientation, where the AA-stacking bilayer MoS 2 has a higher carrier mobility than that of AB-stacking bilayer MoS 2 , and the 30°-twisted bilayer MoS 2 has a higher electrical property than its 0°-twisted bilayer MoS 2 . Thus, the controlling growth of MoS 2 including the thickness and stacking orientation has attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum disulfide (MoS 2 ) as the typical member of two-dimensional (2D) transition metal dichalcogenides (TMDCs) has attracted tremendous attention due to its rich physical/chemical properties, such as layer-dependent electronic structure, layer-dependent photoexcitation, high mobility, and reasonable band gap. Different than other 2D TMDCs, MoS 2 is earth-abundant and environmentally stable. Thus, it has been considered as a promising candidate for post-Moore’s law era. The recent development, such as construct MoS 2 transistors with 1 nm channel, MoS 2 circuits, and MoS 2 room photodetectors with detection range from visible to near-infrared, exhibits its potentials in novel applications like electronic and optoelectronic devices. , Although the monolayer MoS 2 has gained more investigation, more and more research demonstrated that the device based on few-layer MoS 2 has a higher device carrier mobility caused by the lower contact resistance, which is one of the most important factors when evaluating the semiconductor devices. Besides the thickness factor, the electrical property of few-layer MoS 2 is also related to its stacking orientation, where the AA-stacking bilayer MoS 2 has a higher carrier mobility than that of AB-stacking bilayer MoS 2 , and the 30°-twisted bilayer MoS 2 has a higher electrical property than its 0°-twisted bilayer MoS 2 . Thus, the controlling growth of MoS 2 including the thickness and stacking orientation has attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Neither is the WS 2 flake homogeneous as far as electrical and electronic properties are concerned nor is the sample-substrate junction ohmic, especially if the topographic height difference arises from local delamination of a domains. Symmetric segmentation in PL maps [20,50], has been reported before in monolayer flakes and attributed to delamination of alternating domains due to strain induced in the sample from the high temperature growth and subsequent cooling and differential thermal expansion of the sample and substrate. However, transferred flakes of similar size were reported to have strain relaxed, leading to disappearance of segmentation [50], contrary to the present observations.…”
Section: Resultsmentioning
confidence: 56%
“…Symmetric segmentation in PL maps [20,50], has been reported before in monolayer flakes and attributed to delamination of alternating domains due to strain induced in the sample from the high temperature growth and subsequent cooling and differential thermal expansion of the sample and substrate. However, transferred flakes of similar size were reported to have strain relaxed, leading to disappearance of segmentation [50], contrary to the present observations. The IV characteristics shown in figure 3(d) are representative of two back-to-back metalsemiconductor-metal Schottky junctions, which are asymmetric under bias reversal.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Since the discovery of graphene, two-dimensional (2D) semiconductors have inherently shown fascinating characteristics in the development of semiconductor technology and the potential to surpass the atomic limit of silicon platforms. They have combinations of diverse crystal or phase structures, multiple periodic table elements, continuous rotation stacking order (for heterostructures), and, most importantly, adjustable band gaps via thickness, which are expected to have important application potential in the fields of smart optoelectronics. , Transition metal dichalcogenides (TMDs), such as molybdenum sulfide (MoS 2 ), were the earliest studied van der Waals semiconductors with a nonzero band gap, that have been technically reduced to a single atomic layer thickness. Simultaneously, their appealing sensitivity to external stimuli (e.g., heat, strain, and illumination) allows them to be a promising candidate for highly integrated electronic and optoelectronic systems (e.g., photodetectors), ranking among the post-Moore’s Law era. …”
Section: Introductionmentioning
confidence: 99%